METHODOLOGICAL APPROACHES TO STUDYING OF UKRAINIAN AS A FOREIGN LANGUAGE AT MEDICAL INSTITUTIONS OF HIGHER EDUCATION - Tsurkan, Maria (Educological discourse, 2020)
Main methodological approaches to studying of Ukrainian as a foreign language of students from medical institutions of higher education have been described in the article, in particular content and peculiarities have been revealed of such approaches as system, communicative-activity, personally-oriented professionally-oriented, socially-cultural, word-centric, contextual, competency ones. It has been stated, that such structured components are singled out in methodological system of studying of Ukrainian as a foreign language as aim, content, task, approaches, principles, methods, forms, means, technologies and results of studying, which provide implementation of educational process, while interacting between each other. It has been noted, that distinguishing of presented approaches to studying of Ukrainian as a foreign language is implemented according to the aim and tasks of educational disciplines. It has been emphasized, that aim of the discipline «Ukrainian language» consists in achievement of final goals of education, which are basis for construction of its content. Practical acquirement of a language at I medium level is considered as terminal goal of the discipline at medical institutions of higher education, that is sufficient for implementation of cognitive activity in social-cultural and educational-professional spheres, that is realized with the help of complex approach to preparation of future specialists and provides interaction of communicative, educational and disciplinary goals.